In Silico Veritas: The Pitfalls and Challenges of Predicting GPCR-Ligand Interactions - Sander B. Nabuurs; Jan P.G. Klomp; Rob Leurs; Jacob De Vlieg; Iwan J.P. De Esch; Bas Vroling; Marijn P.A. Sanders; Luc Roumen; Chris De Graaf (MDPI AG, 2011)
Recently the first community-wide assessments of the prediction of the structures of complexes between proteins and small molecule ligands have been reported in the so-called GPCR Dock 2008 and 2010 assessments. In the current review we discuss the different steps along the protein-ligand modeling workflow by critically analyzing the modeling strategies we used to predict the structures of protein-ligand complexes we submitted to the recent GPCR Dock 2010 challenge. These representative test cases, focusing on the pharmaceutically relevant G Protein-Coupled Receptors, are used to demonstrate the strengths and challenges of the different modeling methods. Our analysis indicates that the proper performance of the sequence alignment, introduction of structural adjustments guided by experimental data, and the usage of experimental data to identify protein-ligand interactions are critical steps in the protein-ligand modeling protocol.